Unity in diversity : English Puritans and the Puritan Reformation, 1603-1689 - Pederson, Randall J., 1975- (Brill's series in church history, 2014)
In Unity in Diversity, Randall J. Pederson critiques current trends in the study of Puritanism, and proposes a different path for defining Puritanism, centered on unitas and diversitas, by looking at John Downame, Francis Rous, and Tobias Crisp.